ASSESSMENT OF THERAPEUTICAL EQUIVALENCY OF ORIGINAL AND GENERIC INDAPAMIDE IN HYPERTENSIVE PATIENTS BY RANDOMIZED CROSS-OVER STUDY - N. P. Kutishenko; V. V. Yakusevich; A. D. Deev; S. Y. Martsevich (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To develop a protocol for comparison of efficacy and safety of original drugs with generic ones and to apply this protocol for comparison of generic indapamide (Indap) with original indapamide in two presentations: short acting (Arifon) and long acting (Arifon Retard).Materials and methods: 64 patients with arterial hypertension of 1-2 degree took part in open cross-over randomized study. All patients were treated with Indap as well as with Arifon (half of patients) or Arifon Retard (another half) for comparison. Each kind of therapy lasted for 6 weeks; sequence of drug administration was randomized. The effect of treatment was assessed by resting blood pressure (BP) dynamics. If antihypertensive effect was not sufficient after 3 weeks of treatment, lisinopryl (Dapril) 10 mg/d was added.Results. There were no differences between basic clinical characteristics in groups of patients initially treated with different indapamide medications. Systolic and diastolic BP significantly reduced after 3 weeks of treatment without difference between tested indapamide medications. Combined therapy led to additional decrease in BP without significant difference between the patients groups. There was no significant difference in groups on the rates of side effects caused by therapy with tested indapamide medications.Conclusion. The proposed protocol of study showed that there were no significant differences in efficacy and safety of two presentations of original indapamide and tested generic indapamide in hypertension treatment.